Improve Early Reading Skills in Low Classes Through Big Media - Chairina, Ina (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2020)
Reading skill is a skill in recognizing and understanding writing in the form of letters, words, and sentences in reading in order to obtain information contained in the reading. By reading we are able to understand the contents of the world and our thinking patterns develop. Developing the courage of students to want to talk and learn can be developed through education. However, unfortunately reading habits are still considered trivial even there are still many students who find it difficult to read fluently. Therefore, there is a need for media that will deliver to students to wish to read continuously. This study aims to improve early reading skills in the lower classes through the Big Book media.This type of research is classroom action research conducted collaboratively, in which collaborative itself is a situation where there are two or more people studying or trying to learn something together - together. The subjects of this study were grade 1 students at Alwashliyah Elementary School, Medan Marelan District, which consisted of 21 female students and 14 male students. Data collection techniques in this study used tests, observations, and interviews. The qualitative data collection instruments used observation sheets and quantitatively used reading skills tests. The data analysis test used is quantitative and qualitative descriptive data analysis.Keywords: Beginning reading skills, Big Book media